Reducing off-target expression of mRNA therapeutics and vaccines in the liver with microRNA binding sites - Brian J. Parrett; Satoko Yamaoka; Michael A. Barry (Molecular Therapy: Methods & Clinical Development)
Lipid nanoparticles (LNPs) are often liver tropic, presenting challenges for LNP-delivered mRNA therapeutics intended for other tissues, as off-target expression in the liver may increase side effects and modulate immune responses. To avoid off-target expression in the liver, miR-122 binding sites have been used by others in viral and non-viral therapeutics. Here, we use a luciferase reporter system to compare different copy numbers and insertion locations of miR-122 binding sequences to restrict liver expression. We inserted one to five miR-122 binding sites into the 5′ or 3′ untranslated regions (UTRs) of luciferase mRNAs and tested them in LNPs in vitro and in vivo via systemic intravenous and local intramuscular injections in mice. Our results showed no significant differences in de-targeting efficacy between mRNAs harboring one or multiple miR-122 binding sites or between those with 5′ or 3′ UTR placements. To test the impact of miR-122 binding sites on antibody response to a mRNA vaccine, Ebola virus matrix protein VP40 mRNAs were modified with or without miR-122 binding sites and injected in mice intramuscularly. This work reinforces the utility of miR-122 binding sites while providing a comparison of these sites to aid the future development of LNP-mRNA therapies for non-hepatic tissues.